Differences In the Antioxidant Activity of Sungkai Leaf Extract Using Methanol And Aquades Solvents - Dira Irnameria; Yenni Okfrianti (UNIVED Press, Dehasen University Bengkulu, 2023)
The antioxidant activity of natural product extracts is influenced by the type of solvent that plays an active role in binding secondary metabolites such as saponins and flavonoids. Sungkai leaves (Peronema canescens Jack) are plants that have been shown to contain secondary metabolites that have antioxidant activity. The purpose of this study was to determine the differences in the antioxidant activity of Sungkai leaves with different solvents. Sungkai leaves (Peronema canescens Jack) used in this study were obtained in Central Bengkulu Regency, Bengkulu Province. Sungkai leaves are extracted with two types of solvents, namely methanol and distilled water. Furthermore, the analysis of antioxidant activity was carried out using the DPPH method. The results showed that the antioxidant activity of IC50 (inhibitor concentration 50) was 45.709 ppm, which was very strong in methanol extract. Antioxidant activity in distilled water is known to have an IC50 value of 53.979 ppm, which means strong. Furthermore, it can be concluded that the existence of differences in solvents can affect the level of antioxidant activity of Sungkai leaves. Methanol solvent contains stronger antioxidant activity than distilled water.